Find the remainder when f(x) =
![{x}^{5} - {x}^{3} + {3x}^{2} + 3x + 1 {x}^{5} - {x}^{3} + {3x}^{2} + 3x + 1](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B5%7D++-++%7Bx%7D%5E%7B3%7D++%2B++%7B3x%7D%5E%7B2%7D++%2B+3x+%2B+1)
is divided by
![{x}^{2} - 1 {x}^{2} - 1](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-+1)
Answers
Answered by
2
Let's know what the remainder theorem is.
Remainder Theorem → If f(x), a polynomial in x, is divided by (x - a), the remainder = f(a) e.g. If f(x) is divided by (x - 3), the remainder is f(3).
x² - 1 = 0
x² = 1
x = 1 (√1 is 1)
f(x) = x⁵ - x³ + 3x² + 3x + 1
→ Put the value of x.
f(1) = (1)⁵ - (1)³ + 3(1)² + 3(1) + 1
= 1 - 1 + 3 + 3 + 1
= 7
The remainder when f(x) = x⁵ - x³ + 3x² + 3x + 1 is divided by x² - 1 is 7.
Similar questions